A study on the appropriate dose of rocuronium for intraoperative neuromonitoring in Da Vinci robot thyroid surgery: a randomized, double-blind, controlled trial - Lan, Jianning; Huang, Qijian; Su, Jiansheng; Zhang, Xuru; Zhang, Liangcheng (Frontiers in Endocrinology, 2023)
Background: This study was to explore the effect of different doses of rocuronium bromide on neuromonitoring during Da Vinci robot thyroid surgery.Methods: This was a prospective, randomized, double-blind, controlled trial that included 189 patients who underwent Da Vinci robot thyroidectomy with intraoperative neuromonitoring(IONM).Patients were randomly divided into three groups and given three different doses of rocuronium (0.3mg/kg, 0.6mg/kg, 0.9mg/kg). Outcome measurements included IONM evoked potential, postoperative Voice Handicap Index-30(VHI-30), intraoperative body movement incidence rate, Cooper score, and hemodynamic changes during anesthesia induction.The difference in IONM evoked potentials at various time points between the three groups was not statistically significant (P>0.05). The difference in Cooper scores and intraoperative body movement incidence rate between 0.6 and 0.9mg/kg groups was statistically significant compared with the 0.3mg/kg group (both P<0.001). There was no statistically significant difference in VHI-30 score and hemodynamic changes during anesthesia induction among the three groups (both P>0.05).For patients undergoing Da Vinci robot thyroidectomy, a single dose of rocuronium at 0.6 and 0.9mg/kg during anesthesia induction can provide stable IONM evoked potential. Additionally, compared to 0.3 mg/kg, it can offer better tracheal intubation conditions and lower incidence of body movements during surgery. It is worth noting that the use of higher doses of rocuronium should be adjusted based on the duration of IONM and local practices.